Strategic business planning a dynamic system for improving performance & competitive advantage - Reading, Clive; Gale Group (London Kogan Page, 2002)
Outlines a business process which should improve the performance and competitive position of any company. It enables the reader to link company purpose, business goals, strategy, performance targets and an action programme into one framework.
The strategic business planning framework -- Strategic concepts -- The strategic business planning process.
Electronic reproduction.
Keywords: Strategic planning; Business planning; Competitiveness and benchmarking; Electronic books